Activation strategies for invariant natural killer T cells - Kohlgruber, Ayano C. (Immunogenetics, 2016)
Invariant natural killer T (iNKT) cells are a specialized T cell subset that plays an important role in host defense, orchestrating both innate and adaptive immune effector responses against a variety of microbes. Specific microbial lipids and mammalian self lipids displayed by the antigen-presenting molecule CD1d can activate iNKT cells through their semi-invariant αβ T cell receptors (TCRs). iNKT cells also constitutively express receptors for inflammatory cytokines typically secreted by antigen-presenting cells (APCs) after recognition of pathogen-associated molecular patterns (PAMPs), and they can be activated through these cytokine receptors either in combination with TCR signals, or in some cases even in the absence of TCR signaling. During infection, experimental evidence suggests that both TCR-driven and cytokine-driven mechanisms contribute to iNKT cell activation. While the relative contributions of these two signaling mechanisms can vary widely depending on the infectious context, both lipid antigens and PAMPs mediate reciprocal activation of iNKT cells and APCs, leading to downstream activation of multiple other immune cell types to promote pathogen clearance. In this review, we discuss the mechanisms involved in iNKT cell activation during infection, focusing on the central contributions of both lipid antigens and PAMP-induced inflammatory cytokines, and highlight in vivo examples of activation during bacterial, viral, and fungal infections.